Antecedents, outcomes and measurement of work related-cognition in non-work time: A multistudy report using the work-related rumination questionnaire in two languages - Pauli, Roman; Gaum, Petra Maria; Cropley, Mark; Lang, Jessica (Frontiers in Psychology, 2023)
According to the perseverative cognition hypothesis, prolonged activation for example, via work-related rumination impairs recovery and thereby poses a risk to employee health. The extent to which gender, age, occupation or longitudinal stress exposure may alter work-related rumination is an ongoing debate. Whether group or longitudinal comparisons of work-related rumination are valid, however, has never been tested. In this multistudy report, we therefore investigated measurement invariance of the widely used Work-Related Rumination Questionnaire (WRRQ) across gender, age, occupation, and longitudinal measurements by performing secondary analyses of preexisting data on work-related rumination. We examined the psychometric properties of WRRQ measurements in two languages and expand knowledge about the nomological network of affective rumination, problem-solving pondering and detachment in relation to individual employee characteristics (e.g., personality, work engagement, commitment), job stressors (e.g., work intensity, decision latitude, social relations with colleagues and supervisors) and employee health outcomes (e.g., wellbeing, irritation, somatic symptoms). Multigroup confirmatory factor analyses showed partial scalar invariance of English and German WRRQ measurements and full scalar invariance across gender, age, occupation and over the period of 1 week (Study 1, n = 2,207). Correlation analyses supported criterion, convergent and discriminant validity of WRRQ measurements (Study 2, n = 4,002). These findings represent a prerequisite for comparisons of work-related cognition across groups and further the understanding of the antecedents and outcomes of different types of work-related cognition.